The Influence of Financial Well-Being on Happiness and Financial Decision Making in Indonesia - Dewi, Fransiska; Purwantoro, R Nugroho (Sekolah Tinggi Manajemen IPMI, 2024)
Previous studies have investigated the effect of financial well-being on happiness, and emotions on financial decision making, but there were not many that have combined both. This research aims to reveal the effect of financial well-being on happiness, and the effect of happiness on financial decision-making among Indonesians. Source of financial well-being, province, and gender are included as moderating variables to the relationship between financial well-being and happiness. The analysis examined primary data from a sample of 152 respondents across the country with PLS-SEM and secondary data from World Happiness Report, GDP/capita, amount of saving in general bank and retirement saving for Indonesians with regression. Based on analysis on the primary and secondary data, financial well-being has positive correlation with happiness, and happiness has positive correlation with financial decisions. However, based on analysis from the primary data, there are no effect from all moderating variables. This research adds to the literature of financial well-being, happiness, and financial decision making, and its findings also provide opportunities for future research within the fields.